Craters, boulders and regolith of (101955) Bennu indicative of an old and dynamic surface - Walsh, KJ; Jawin, ER; Ballouz, R-L; Barnouin, OS; Bierhaus, EB; Jr, CHC; Molaro, JL; McCoy, TJ; Delbo', M; Hartzell, CM; Pajola, M; Schwartz, SR; et al. (Springer Nature, 2019)
Small, kilometre-sized near-Earth asteroids are expected to have young and frequently refreshed surfaces for two reasons: collisional disruptions are frequent in the main asteroid belt where they originate, and thermal or tidal processes act on them once they become near-Earth asteroids. Here we present early measurements of numerous large candidate impact craters on near-Earth asteroid (101955) Bennu by the OSIRIS-REx (Origins, Spectral Interpretation, Resource Identification, and Security-Regolith Explorer) mission, which indicate a surface that is between 100 million and 1 billion years old, predating Bennu’s expected duration as a near-Earth asteroid. We also observe many fractured boulders, the morphology of which suggests an influence of impact or thermal processes over a considerable amount of time since the boulders were exposed at the surface. However, the surface also shows signs of more recent mass movement: clusters of boulders at topographic lows, a deficiency of small craters and infill of large craters. The oldest features likely record events from Bennu’s time in the main asteroid belt.